Analisis Keterampilan Berkolaborasi Mahasiswa Calon Pendidik IPA pada Mata Kuliah IPBA - Indri Nurwahidah; Dwi Septiana Sari (Yayasan Literasi Sains Indonesia, 2025)
Collaboration skills are one of the skills that support 21st-century learning. Collaboration skills need to be mastered by prospective science educator students as a provision in teaching. The purpose of this study was to determine the collaboration skills of prospective science educator students in the Science and Mathematics subject. The type of research used was descriptive qualitative. The study was conducted in the even semester of the 2024-2025 academic year in the Science and Mathematics subject involving 16 students. Observations were made directly during the learning process using an observation sheet with five indicators of collaboration skills. The results showed that the collaboration skills of prospective science educator students were quite good with an average score of 74.33. The best skill was found in the indicator of sharing responsibilities in groups with a score of 81.25 while the lowest indicator was found in the indicator of working productively in groups with a score of 65.63. Based on the results of the study, it can be concluded that overall the collaboration skills of prospective science educator students were quite good, but still need to be improved. This can be used as a reference in developing the collaboration skills of prospective educator students.